Islam & travel in the Middle Ages - Touati, Houari (The University of Chicago Press, 2010)
[This book] assesses both the religious and philosophical aspects of travel, as well as the economic and cultural conditions that made the rihla possible. Houari Touati tracks the compilers of the hadith who culled oral traditions linked to the prophet, the linguists and lexicologists who journeyed to the desert to learn Bedouin Arabic, the geographers who mapped the Muslim world, and the students who ventured to study with holy men and scholars. Travel, with its costs, discomforts, and dangers, emerges in this study as both a means of spiritual growth and a metaphor for progress. Touati's book will interest a broad range of scholars in history, literature, and anthropology.